2018
DOI: 10.4317/medoral.22326
|View full text |Cite
|
Sign up to set email alerts
|

Survival study of leukoplakia malignant transformation in a region of northern Spain

Abstract: BackgroundOral leukoplakia is the most common potentially malignant disorder (PMD) of the oral cavity. The objectives of this study are to determine the clinicopathologic features in a group of patients with oral leukoplakia of Northern Spain (Galicia), determining the factors associated to clinical risk and analyzing the malignant transformation of these patients.Material and MethodsWe included 85 patients. We recorded sex and age, habits like alcohol and tobacco, size, clinical appearance, site, number of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
46
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(62 citation statements)
references
References 39 publications
14
46
1
1
Order By: Relevance
“…In our series, non-homogeneous lesions were associated to a significant increase in malignization risk. This is consistent with the findings of Gándara-Vila et al ( 24 ), who reported a 5-fold greater risk of malignant transformation in the case of non-homogeneous lesions versus homogeneous lesions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our series, non-homogeneous lesions were associated to a significant increase in malignization risk. This is consistent with the findings of Gándara-Vila et al ( 24 ), who reported a 5-fold greater risk of malignant transformation in the case of non-homogeneous lesions versus homogeneous lesions.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, 8.3% of the lesions exhibited malignant transformation to oral squamous cell carcinoma. Gándara-Vila et al ( 24 ) reported a very similar percentage (8.2%) after an average of 5.58 years of follow-up among their patients with OL. Einhorn and Wersall ( 25 ) studied 782 patients with a mean duration of follow-up of 11.7 years, and recorded a 3.93% malignization rate.…”
Section: Discussionmentioning
confidence: 74%
“…However, the efficacy of histopathological grading of dysplasia as an indicator of malignant transformation remains controversial. In our study, the Kaplan–Meier survival analysis indicated that a higher severity of dysplasia was associated with a higher risk of malignant transformation, which was consistent with most of the published studies (Gandara‐Vila et al., 2018; Liu et al., 2010) and in keeping with the concept of multistep process of accumulation of mutations and epigenetic alterations. Nevertheless, other studies have found no significant association between a higher severity of dysplasia and an increased risk of malignant transformation (Dost, Cao, Ford, Ades, & Farah, 2014; Tilakaratne, Sherriff, Morgan, & Odell, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Our study confirmed that the lesions located on the ventral surface of the tongue or floor of the mouth were significantly more likely to develop into OSCC than lesions in other sites, which is consistent with previous studies (Anderson & Ishak, 2015; Monica et al., 2015). An acceptable explanation for the susceptibility of carcinogenesis might be that certain anatomical sites may have the unique histological characteristic of lacking a protective keratin layer (Gandara‐Vila et al., 2018; Mashberg & Meyers, 1976) and might be more readily penetrated by carcinogens, such as tobacco and alcohol (Schepman, Bezemer, van der Meij, Smeele, & van der Waal, 2001). This study also confirmed the significantly higher probability of malignant development of the non‐homogenous rather than homogenous type of OLK with a hazard ratio of 3.0, suggesting the use of an optimal biopsy site and shorter follow‐up interval for such high‐risk patients (Holmstrup, Vedtofte, Reibel, & Stoltze, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The region of jugal mucosa was the most frequent site of involvement in this study. The oral tongue and the floor of the mouth are the sites of major involvement of the OEDs (Gandara-Vila et al, 2018;Speight et al, 2018), and are also considered anatomical sites of high risk for malignant transformation, this location is almost always related to etiologic factors and therefore may vary by geo Figure location and local habits (Speight et al, 2018).…”
Section: Discussionmentioning
confidence: 99%